Awareness of Internet of Things (IoT) Applications for Learning Enrichment among Undergraduate Students - Makinde, Semiu Olawale; Ibrahim, Rahmat Bolatito; Ibrahim, Taye; Ganiyu, Rasidat Sade (ASEAN Journal of Educational Research and Technology, 2025)
The shift from traditional to technology-driven learning has brought numerous advantages, with the Internet of Things (IoT) emerging as a promising avenue for enhancing educational experiences. Despite its potential, undergraduates have not fully embraced IoT for learning, primarily due to a lack of awareness. This study investigates the awareness of IoT among undergraduates, considering gender and area of specialization. Using a descriptive survey method, the research focuses on undergraduates in Kwara State universities, employing random and stratified sampling. Data collection utilized a validated questionnaire, and analysis involved percentages, mean scores, t-tests, and Analysis of Variance (ANOVA). Findings revealed smartphones as the most widely used IoT devices. Gender significantly influenced IoT awareness. However, the area of specialization did not significantly impact awareness. Conclusively, undergraduates are employing IoT devices for learning, emphasizing the need for heightened awareness among female students and encouraging widespread utilization of these technologies for improved educational experiences.